Analisis Kandungan Mineral Air Tanah dan Gambaran Status Karies Gigi pada Masyarakat Desa Mala Kepulauan Talaud - Sagemba, Pascal G.; Mintjelungan, Christy N.; Kepel, Billy J. (e-GiGi, 2025)
Abstract: Elements present in ground water can be influenced by the surrounding environment. High levels of fluorine and calcium in ground water can have an impact on public health, including dental health. The most common dental and oral health problem in people of all age groups is dental caries. This study aimed to analyze the mineral content of ground water and to describe the status of dental caries in the community at Desa Mala. This was a descriptive study with a cross-sectional design using total sampling of age group of 20-50 years with a population of 110 people. Water samples were tested in the laboratory for its fluoride content and hardness. The results obtained 74 people as subjects according to the inclusion and exclusion criteria. Fluorine content in drinking water samples was 0.36 mg/L and the hardness (CaCO3) was 294 mg/L. The average of DMF-T index measurement of dental caries of subjects was 7.6. In conclusion, the fluoride level and hardness of the well water in the Desa Mala community is suitable for drinking, however, the dental caries profile in the community is very high. Keywords: mineral content of groundwater; dental caries status; fluor; calcium    Abstrak: Unsur-unsur yang ada dalam air, dapat dipengaruhi oleh lingkungan sekitar. Kadar fluor dan kalsium yang tinggi dalam air dapat berdampak pada kesehatan masyarakat termasuk kesehatan gigi. Masalah kesehatan gigi dan mulut yang paling banyak ditemui pada masyarakat dengan berbagai golongan umur ialah karies gigi. Penelitian ini bertujuan untuk menganalisis kandungan mineral air dalam tanah dan mengetahui gambaran status karies gigi pada masyarakat di Desa Mala. Jenis penelitian ialah deskriptif dengan desain potong lintang dengan total sampling pada golongan usia 20–50 tahun dengan jumlah populasi 110 orang serta melakukan uji sampel air di laboratorium untuk menguji fluor dan kesadahan dalam air. Hasil penelitian mendapatkan 74 orang sesuai dengan kriteria inklusi dan ekslusi. Kandungan fluor dalam air minum sebesar 0,36 mg/L dan kesadahan (CaCO3) sebesar 294 mg/L. Hasil pengukuran indeks DMF-T karies gigi pada sampel penelitian sebesar 7,6. Simpulan penelitian ini ialah kadar fluor dan kesadahan air sumur di Desa Mala masih layak untuk diminum sedangkan gambaran karies gigi pada masyarakat tergolong masih sangat tinggi. Kata kunci: kandungan mineral air tanah; status karies gigi; fluor; kalsium